An efficient content sharing scheme using file splitting and differences between versions in hybrid peer-to-peer networks. (18th July 2019) - Hayashi, Toshinobu; Sugawara, Shinji
This paper proposes an efficient content sharing strategy using file splitting and difference between versions in hybrid Peer-to-Peer (P2P) networks. In this strategy, when a user requests a content item, he/she can get it from the network by retrieving the other version of the content item and the difference from the requested version, if the obtaining cost of the requested version is expensive. This way of content sharing can be expected to accomplish effective and flexible operation. Furthermore, efficient utilisation of a peer's storage capacity is achieved by splitting each replica of a content item into several small blocks and storing them separately in the plural peers.